СТРАТЕГІЧНИЙ АНАЛІЗ ГУДВІЛУ В ОБЛІКОВО- АНАЛІТИЧНІЙ СИСТЕМІ ПІДПРИЄМСТВА - Судин, Юлія Анатоліївна (Науковий журнал «Світ фінансів», 2017)
Судин Ю. А. Стратегічний аналіз гудвілу в обліково-аналітичній системі підприємства. Розглянуто сутність гудвілу та особливості його визначення у контексті стратегічних активів підприємства. Розкрито мету, завдання, джерела інформації та основні етапи стратегічного аналізу гудвілу. Проведено моніторинг ресурсів та шляхів формування гудвілу на підприємстві. Визначено та систематизовано зовнішні і внутрішні фактори пливу на формування ділової репутації компанії. Проведено емпіричну апробацію факторного аналізу та установлено пріоритетність впливу чинників на формування гудвілу підприємств. Судын Ю. А. Стратегический анализ гудвилла в учетно-аналитической системе предприятия. Рассмотрены сущность гудвилла и особенности его определения в контексте стратегических активов. Раскрыты цели, задачи, источники информации и основные этапы стратегического анализа гудвилла. Проведен мониторинг ресурсов и путей формирования гудвилла на предприятии. Определены и систематизированы внешние и внутренние факторы влияния на формирование деловой репутации компании. Проведена эмпирическая апробация факторного анализа и установлено приоритетность влияния факторов на формирование гудвилла предприятий. Sudyn Yu. Strategic analysis of goodwill in accounting and analytical systems of enterprises. Introduction. One of the essential assets that has significant impact on the investment attractiveness of the enterprise is goodwill. Due to its interpretation and variation in approaches, goodwill generates plenty discussions and is one of the most problematic research question in general accounting methodology. Purpose. To improve the assessment regulations for goodwill from the perspective of a modern economic environment. Results. Goodwill and its components such as level of quality control, reliability, buyers, trade secret, highly skilled workers and research are not reflected in the financial statements. However, many researchers insist the correct and appropriate assessment should help to show them as assets in financial reporting. Some authors tell that more and more companies realize that their advantage is not in the hardware but intangible assets such as the brain power of a corporation. Three-quarters of value added in manufacturing is obtained through knowledge. Existing restrictions on the recognition and measurement of certain types of intangible assets do not allow them to be recognized as an object of accounting. Conclusion. Since studies have shown that disclosures about goodwill are often not compliant with the rules in accounting standards, the research aims to analyze the characteristics of goodwill accounting from the perspective of a posttransition country. The analysis includes Ukrainian publicly quoted companies and the results show that goodwill is on average less important in comparison with traditionally developed market economies. The content analysis of disclosures provides evidence about strengths and weaknesses of goodwill disclosure.